Proactive interception and care of Frailty and Multimorbidity in older persons: the experience of the European Innovation Partnership on Active and Healthy Ageing and the response of Parma Local Health Trust and Lab through European Projects: Proactive response to frailty and multimorbidity - Longobucco, Yari; Benedetti, Chiara; Tagliaferri, Sara; Angileri, Vincenza Valentina; Adorni, Elisa; Pessina, Michele; Zerbinati, Luna; Cicala, Lorenzo; Pelà, Giovanna; Giacomini, Vittoria; Barbolini, Mirca; Lauretani, Fulvio; et al. (Acta Biomedica Atenei Parmensis, 2019)
According to the 2018 European Union Ageing Report, the demographic profile of the European population is projected to be older. Aging cannot be considered a homogeneous process, and only in certain cases is “successful”, with maintained functional ability, which is determined by intrinsic capacity, the environment, and their interaction. When intrinsic capacity is lost, elders with chronic diseases develop frailty, a condition with high-risk of disability. Old-age dependency-ratio is projected to increase from 29.6% to 51.2% in the EU in 2070: thus, the need of new approaches targeting the prevention of disability. Numerous studies are conducted in the European Innovation Partnership on Active and Healthy Ageing and addressing identification, treatment, coordination and integration of care in frail older subjects. SUNFRAIL is aimed at developing a model, good practices and tools to improve the identification, prevention and care of frailty and management of multimorbidity. SPRINTT is testing the effectiveness of a multi-component treatment able to treat frailty and sarcopenia. VIGOUR, a project aimed at strengthening integrated-care in different contexts of European Countries, verifies enablers and obstacles encountered in the real world by these good practices. Through the creation of Parma-Lab and Frailty-Team in the Academic-Hospital of Parma combined with the contribution of Parma Health-Trust in the “Community Health-Centers”, the Projects were translated into Health Services Arena. This response bridging European Studies and clinical practice, aims to early detecting and caring 75-year older citizens with frailty and multimorbidity, living in the community, not institutionalized and at risk of hospitalization and mobility ADL-disability.